THE CORRELATION BETWEEN THE STUDENTS’ MOTIVATION IN LEARNING ENGLISH AND THEIR READING COMPREHENSION AT THE EIGHTH GRADE STUDENTS OF SMPN 2 LEMBAH MELINTANG - KAROLINA, PUSPITA (BRIGHT VISION Journal of Language and Education, 2022)
This research aimed to find out there is correlation between students’ motivation in learning English and their reading comprehension students of SMPN 2 Lembah Melintang. The research methodology was quantitative research by using correlational method. The population of this research was eighth grade students of SMPN 2 Lembah Melintang. The samples of this research were 30 students of SMPN 2 Lembah Melintang used simple random sampling. The instruments of this research students’ motivation questionnaire and reading comprehension test. After analyze the data used statistic calculation, the results of this research showed that there was positive significant correlation between the students’ motivation in learning English and their reading comprehension at the eighth grade students of SMPN 2 Lembah Melintang. Which rvalue = 0,963> rtable 5% = 0,361.